A new chaos particle swarm optimisation algorithm and its applications for transportation continuous network design problem. (1st January 2012) - Ma, Changxi; Li, Yinzhen; He, Ruichun; Chen, Zhizhong; Qi, Bo; Diao, Aixia
In order to overcome the drawback of basic particle swarm optimisation algorithm, such as being subject to fall into local optimisation and being poor in performance of precision, a chaos multi-population particle swarm optimisation algorithm has been proposed, and the algorithm has been effectively used in dealing with the optimisation of transportation continuous network design problem. In this algorithm, multi-population parallel tactics are introduced to improve the global optimising ability and the chaotic search which behaves well in local searching is introduced to improve the solution. The transportation continuous network design problem is solved based on chaos multi-population particle swarm optimisation algorithm. Two examples are presented to compare the proposed method with some existing algorithms. The simulation results show the new particle swarm optimisation algorithm can effectively alleviate the problem of premature convergence and strengthen the global searching ability. The algorithm presented in the paper can apply to solve the large scale traffic design problems.